2013
DOI: 10.1002/jemt.22294
|View full text |Cite
|
Sign up to set email alerts
|

Multi-label classification for colon cancer using histopathological images

Abstract: Colon cancer classification has a significant guidance value in clinical diagnoses and medical prognoses. The classification of colon cancers with high accuracy is the premise of efficient treatment. Our task is to build a system for colon cancer detection and classification based on slide histopathological images. Some former researches focus on single label classification. Through analyzing large amount of colon cancer images, we found that one image may contain cancer regions of multiple types. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Previous publications have demonstrated that combined radiomic features can offer good performance for multi-label colon cancer prediction, with a precision of 73.7% ( 41 ). However, colon cancer diagnosis and prognosis depends on the ability to discriminate between the distinct malignancy states which can exist ( 42 ), oftentimes within an individual tumor section.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have demonstrated that combined radiomic features can offer good performance for multi-label colon cancer prediction, with a precision of 73.7% ( 41 ). However, colon cancer diagnosis and prognosis depends on the ability to discriminate between the distinct malignancy states which can exist ( 42 ), oftentimes within an individual tumor section.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, multilabel classification of colon cancer using histopathological images was performed using several types of features. It was concluded that combined features can offer good performance for multilabel colon cancer prediction, with a precision of 73.7% [ 32 ]. Moreover, another study has proven that colon cancer prognosis can be identified by using distinct molecular subtypes and serrated precursor lesions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that several predictors which can deal with both single and multiple type problems have been established, much work should made in this area. For example, there are many computational methods which were proposed for predicting protein subcellular localization, distinguishing functional genomics and text categorization; sentiment classification; classifying colon cancer; recognizing protein function . Encouraged by the success of multi‐Label classification and ensemble teachnique, the present study developed a phosphorylation protein predictor, called Multi‐iPPseEvo, specialized for human proteins by improving the aforementioned shortcomings.…”
Section: Introductionmentioning
confidence: 99%